Estudo das propriedades de funções tratadas no Ensino Médio: uma abordagem através do Cálculo Diferencial - Pereira, André Renan (2022)
The Differential and Integral Calculus subject is known by students as a difficult subject, with a high failure rate. And this causes negative emotions in these students, providing blockages and further increasing their chance of failure. What some of them do not know is that this subject has already formed part of the basic education curriculum, being definitively excluded from the curriculum in the 1960s with the Modern Mathematics Movement. However, the absence of the curriculum does not imply a ban on studying Differential Calculus during High School. In this context, the present work proposes to approach some strategies of how the Differential Calculus can be inserted in the High School, in the study of the properties of functions. Since in the studies of functions and their properties, it is common for High School students to deal with rate of change, maximum and minimum points and also the concept of approximation. In this way, the familiarization of some ideas of Differential Calculus can help the understanding of concepts linked to the functions studied in High School, giving more meaning to the studies, avoiding a simple accumulation of formulas and the memorization of concepts. It can also help students who intend to continue in the area of Exact Sciences, as the early familiarization of concepts linked to Differential and Integral Calculus humanizes the discipline, avoiding blocks in learning.